PERLINDUNGAN HUKUM TERHADAP HAK-HAK ANAK ATAS PENDIDIKAN PADA MASA PANDEMI COVID-19 [The Legal Protection of Children's Right to Education during the Covid-19 Pandemic] - Cynthia Phillo; Hessa Arteja; M Faiz Rizqi (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2021)
Children as the forerunners of the successor to the future Indonesia nation make children individuals who become priorities in holding the right to education. The law itself has governed the rights that a child must have, including the right to get a proper education. Due to the COVID-19 Pandemic, the government finds it difficult in providing legal protection for a proper education rights of children. By using normative legal method, this paper will explain how the legal protection of children’s rights over education during the COVID-19 Pandemic that’s happening and how the government’s role is in fulfilling childern’s rights in getitng an education.Bahasa Indonesia Abstrak: Anak sebagai cikal bakal penerus bangsa Indonesia menjadikan anak sebagai individu yang menjadi prioritas dalam memegang hak pendidikan. Undang-undang sendiri telah mengatur tentang hak-hak yang harus diteirma oleh anak, termasuk hak dalam pendidikan. Karena Pandemi COVID-19 yang terjadi, menambah kesulitan bagi pemerintah untuk memberikan perilundungan hukum bagi hak anak atas pendidikan. Dengan menggunakan penelitian hukum normatif, tulisan ini akan menjelaskan bagaimana perlindungan hukum hak anak atas pendidikan pada masa Pandemi COVID-19 yang sedang tejadi dan bagaimana peran negara dalam memenuhi hak anak dalam mendapat pendidikan.